Structural characterization and antioxidant activity of a glycoprotein isolated from Camellia oleifera Abel seeds against D-galactose-induced oxidative stress in mice. (January 2020) - Li, Tingting; Wu, Cai-e; Meng, Xiangyong; Fan, Gongjian; Cao, Yunfeng; Ying, Ruifeng; Tang, Ying
Graphical abstract: Highlights: A glycoprotein (COG2a) from Camellia. Oleifera Abel seed exhibits antioxidant activity. COG2a has the characteristic structure of an O-linked glycoprotein. COG2a protects against D-galactose-induced oxidative damage in vivo. Abstract: A bioactive glycoprotein (COG2a) was isolated from the seeds of Camellia oleifera Abel by multiple column chromatography and its structure and antioxidant capacity were investigated in vitro and in vivo . Structural analysis of COG2a revealed that it was an O-linked glycoprotein with a molecular mass of 25.9 kDa. The protein and carbohydrate contents of COG2a were 54.28% and 45.29% respectively, and its carbohydrate moieties were mainly rhamnose, arabinose, xylose, mannose, glucose, and galactose at a molar ratio of 1.29:1.65:5.81:1:16.15:14.47. Fourier transform infrared and circular dichroism spectra of COG2a exhibited the typical characteristics of a glycoprotein, that is, 80.3% α-helix, 1.0% β-strand, 6.4% β-turns, and 15.8% unordered residues. COG2a exhibited concentration-dependent free radicals-scavenging capacity in vitro . COG2a also significantly enhanced the SOD and GSH-PX activities and reduced the MDA and total carbonyl contents in blood and liver tissues of D-galactose-induced mice to protect against oxidative stress.